2022
DOI: 10.1371/journal.pgen.1010107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonrandom selection mechanisms on the causal effect estimation for two-sample Mendelian randomization methods

Abstract: Nonrandom selection in one-sample Mendelian Randomization (MR) results in biased estimates and inflated type I error rates only when the selection effects are sufficiently large. In two-sample MR, the different selection mechanisms in two samples may more seriously affect the causal effect estimation. Firstly, we propose sufficient conditions for causal effect invariance under different selection mechanisms using two-sample MR methods. In the simulation study, we consider 49 possible selection mechanisms in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This indicates that there is no causal relationship between insomnia symptoms and pan-cancer risk and that insomnia symptoms might be related to the increased pan-cancer incidence by interfering with multiple factors. Many conventional observational studies suggest that the evening chronotype is associated with an increased risk of some types of cancer ( Erren et al, 2015 ; Hurley et al, 2019 ; Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Von Behren et al, 2021 ; Xie et al, 2021 ; Costas et al, 2022 ; Peeri et al, 2022 ; Yu et al, 2022 ; Yuan et al, 2023 ). However, only a few studies analysed the causal association between chronotype and cancer risk ( Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Yu et al, 2022 ; Yuan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that there is no causal relationship between insomnia symptoms and pan-cancer risk and that insomnia symptoms might be related to the increased pan-cancer incidence by interfering with multiple factors. Many conventional observational studies suggest that the evening chronotype is associated with an increased risk of some types of cancer ( Erren et al, 2015 ; Hurley et al, 2019 ; Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Von Behren et al, 2021 ; Xie et al, 2021 ; Costas et al, 2022 ; Peeri et al, 2022 ; Yu et al, 2022 ; Yuan et al, 2023 ). However, only a few studies analysed the causal association between chronotype and cancer risk ( Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Yu et al, 2022 ; Yuan et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many conventional observational studies suggest that the evening chronotype is associated with an increased risk of some types of cancer ( Erren et al, 2015 ; Hurley et al, 2019 ; Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Von Behren et al, 2021 ; Xie et al, 2021 ; Costas et al, 2022 ; Peeri et al, 2022 ; Yu et al, 2022 ; Yuan et al, 2023 ). However, only a few studies analysed the causal association between chronotype and cancer risk ( Richmond et al, 2019 ; Wang J. et al, 2021 ; Sun et al, 2021 ; Yu et al, 2022 ; Yuan et al, 2023 ). Our study explored the correlations and causal associations between evening chronotype and pan-cancer risk using multivariable Cox proportional hazard and MR analyses simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Many conventional observational studies have suggested that the evening chronotype is associated with an increased risk of some cancers 2,8-10,29−35 . However, only a few studies have analyzed the causal association between chronotype and cancer risk 2,9,32, 33,35 , and few studies have simultaneously explored the causal relationship between de nite evening/morning chronotypes and pan-cancer incidence using their respective SNPs. Our study explored the correlations and causal associations between chronotype and pan-cancer risk using multivariable Cox proportional hazard and MR analyses, which could illustrate the causal relationship and provide better convincing power.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the existing relevant MR studies were carried out in Europeans and mainly focused on central obesity-related indicators [18][19][20]. Although it is advocated to apply multiple MR methods in two-sample MR studies [21], previous studies mainly focused on the results from inversevariance weighted (IVW), weighted median (WM), penalized weighted median (PWM), and MR-Egger methods [15][16][17]22,23]. Based on this, our study aimed to use summary-level data from the Japanese population to elucidate the association between metabolic traits and IS by employing both two-sample and multivariable MR. Additionally, to mitigate bias arising from pleiotropy, our findings were verified by various MR methods.…”
Section: Introductionmentioning
confidence: 99%